1975
DOI: 10.1152/jappl.1975.39.5.812
|View full text |Cite
|
Sign up to set email alerts
|

Localization of the medullary respiratory neurons in rats by microelectrode recording

Abstract: Neuronal activity has been recorded extracellularly from the medulla of anesthetized rats. Units whose discharge frequency varied in phase with respiratory airflow were located bilaterally between 1.5 and 2 mm lateral to midline, extending from 1 mm caudal to 1.5 mm rostral to the obex, in the ventral two-thirds of the medulla. Expiratory units predominated and were intermingled with inspiratory units. Ten different patterns of discharge were distinguished, varying from a short burst at the beginning of expira… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

1986
1986
2010
2010

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(4 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…Since the phrenic nerve activity was not recorded in these experiments, we are not in a position to relate these neurons clearly to the generation or transmission of central respiratory activity. However, the present results are consistent with this idea, as demonstrated by others using extracellular recording techniques (Howard and Tabatabai, 1975). The average of the neuronal membrane potentials triggered by arterial pressure pulse was flat in these RVLM neurons (Fig.…”
Section: Recording From Noncardiovascular Neuronssupporting
confidence: 94%
“…Since the phrenic nerve activity was not recorded in these experiments, we are not in a position to relate these neurons clearly to the generation or transmission of central respiratory activity. However, the present results are consistent with this idea, as demonstrated by others using extracellular recording techniques (Howard and Tabatabai, 1975). The average of the neuronal membrane potentials triggered by arterial pressure pulse was flat in these RVLM neurons (Fig.…”
Section: Recording From Noncardiovascular Neuronssupporting
confidence: 94%
“…Our quantitative EM data suggest that glycinergic terminals comprise about 30% of all synaptic terminals in the interstitial, dorso-medial/lateral and ventrolateral subnuclei, but only about 17% in the commissural and gelatinosus subnuclei. The areas of the NTS most densely innervated by glycinergic fibres do not correspond rigidly to functionally specific regions of the nucleus, but include termination sites of afferent fibres subserving cardiorespiratory functions, as identified in rodents by experiments involving neuronal tracing (Kalia and Sullivan, 1982;Housley et al, 1987;Ciriello et al, 1994) and electrophysiological recording (Howard and Tabatabai, 1975;Paton et al, 1991;Deuchars et al, 2000;Ezure et al, 2002;Kubin et al, 2006).…”
Section: Distribution Of Glycinergic Neurones In the Ntsmentioning
confidence: 99%
“…The first reports on the adult rat respiratory network suggested that the medullary respiratory neurons might be located in the VRG and DRG groups (202,413). The existence of the DRG has been questioned, however (118,344,491), and the results of both in vitro neonatal brain stem preparations and in vivo adult experiments have shown that it may not in fact exist in the rat (193).…”
Section: Adult Rat Medullary Networkmentioning
confidence: 99%